GERIATRIC MORBIDITY PROFILE IN AN URBAN SLUM, CENTRAL INDIA - Singh, J P; Singh, S; Kasturwar, N B; Hassan, A (Indian Journal of Community Health, 2013)
Background – In developing country like India, the elderly people suffer from the dual medical problems of both communicable as well as degenerative diseases. The common illnesses were degenerative disease, cataract, hypertension, diabetes and diseases of locomotors. Methods- The cross sectional study was conducted from Nov 2009 to March2011 in urban slum areas of UHTC, covering a population of 20342, which is an adopted area under the administrative control of dept. of community medicine, NKP Salve Institute of medical sciences & research centre, Nagpur. A minimum sample size of 400 elderly people (>60 yrs) were selected for study by house to house visits and worked out assuming ‘p’ of 50% and precision of 10% at 95% confidence interval. The first house was selected by lottery method and then every 3rd house was selected by systematic random sampling method. Information about study was given to all study subjects, rapport was developed and then subjects were called at UHTC for detailed history and examination. Results-The most common morbidities identified in study population was Anemia (96.50%) followed by Hypertension (34.75%), Arthritis (32.25%), Cataract (21.00%) and Diabetes 17.75%). The significant association of obesity with gender is observed in the present study. Conclusions- Majority of the population above 60 years of age in the present study were suffering from non-communicable diseases. There was a significantly higher load of old age related morbidity among the study subjects. This burden increased with advancement of age possibly as a consequence to progressive multi-organ degeneration and lowered immunologic status involving one body system after another.